The Baseline of Multicultural Education: An Examination from Islamic and Buddhist Standpoints - Wiranto, Erham Budi; Suranto; Muhammad Maga Sule; Nagoor Gafoordeen (Multicultural Islamic Education Review, 2023)
This paper examines the fundamental principles of multicultural education within the philosophical frameworks of Buddhism and Islam. The significance of this subject lies in the fact that the examination of multicultural education is mostly focused on accounts of educational reform methods and movements, with very little exploration of the theoretical underpinnings and conceptual elements, particularly in relation to the philosophical foundations of multicultural education. This report compiles data from many literary sources, employing a qualitative analysis approach. This study scrutinizes the comparative analysis of multicultural education through the lens of Buddhism and Islam, utilizing a conceptual framework that emphasizes the investigation of ontology, epistemology, and axiology as key variables for comparison. The study revealed that there exist conceptual distinctions in the context of multiculturalism when comparing Buddhism and Islam. Divergences arise due to the distinct historical foundations of Islam and Buddhism. However, it is essential to note that there exist inherent similarities in the domains of ontology, epistemology, and axiology, thus indicating a convergence between Islam and Buddhism in the context of developing a multicultural framework for education. Islamic philosophy and Buddhist philosophy offer a solid foundation for the practical application of multicultural education.